(untitled) (Филолошки студии, 2019)
The city of Ohrid, in all of its artistic renditions and designs, affirms the celebration of the Saints Constantine and Helena, lending itself as the authentic interpreter of their cult. Their cult status, as founders of Christianity, can be traced in Ohrid through the commissioning and construction of a temple that has them for its patrons, as well as through their constant presence in the decorative and conceptual system of the frescos and icons of Ohrid, which in turn may be analyzed from the standpoint of the content and the illustrations of their hagiographies as edited by the Eastern Orthodox Church. The Church of Sts. Constantine and Helen belongs to that chapter of artistic creation that stands as a kind of a separate, encircled, chronological and stylistic whole, comprised of the last fifty years of the life of the city of Ohrid, right before the onset of the Turks. The Ohrid monument in honor of the Sts. Constantine and Helen, with its cycle of scenes focused on depicting a number of events, can be examined primarily as an illustration from the hagiographies of these personages in accordance with their treatment by the Eastern Orthodox Church. This study aims at tracing the apparent connection (bond) between the cults of the Sts. Constantine and Helen and the cults of St. Clement of Ohrid and St. Ahil of Larissa, in the regions of Ohrid and Prespa. The analysis of the cult of Constantine and Helen, to a great extent, is confined to the period of the 14th and 15th centuries, when, due to the newly found political circumstances, imposed as such by the Ottoman Turkish conquest, a new need emerged, for new forms of safeguarding Christianity.